Global Capital Flows and Financing Constraints - Harrison, Ann E.; Love, Inessa; McMillan, Margaret S. (World Bank, Washington, DC, 2013)
Firms often cite financing constraints as one of their primary obstacles to investment. Global capital flows, by bringing in scarce capital, may ease the financing constraints of host country firms. But if incoming foreign investors borrow heavily from domestic banks, foreign direct investment may exacerbate financing constraints by crowding host country firms out of domestic capital markets. Combining a unique cross-country firm-level panel with time-series data on restrictions on international transactions and capital flows, Harrison, Love, and McMillan find that different measures of global flows are associated with a reduction in firm-level financing constraints. First, the authors show that one type of capital inflow-foreign direct investment-is associated with a reduction in financing constraints. Second, they test whether restrictions on international transactions affects the financing constraints of firms. The results suggest that only one type of restriction-those on capital account transactions-negatively affects firms' financing constraints. The authors also show that multinational firms are not financially constrained and do not appear to be sensitive to the level of foreign direct investment. This implies that foreign direct investment eases financing constraints for non-multinational firms. Finally, the authors show that (1) foreign direct investment only eases financing constraints in the non-G7 countries, and (2) other kinds of flows, such as portfolio investment, have no impact on financing constraints.